The Impact of Self-Efficacy Analysis-Based Psychological Theory and Literary Ethics on Chinese American Entrepreneurship Education - Li, Hang; Wang, Junsheng; Zhang, Yunyu; Li, Hongmei; Chen, Xialu (Frontiers in Psychology, 2020)
In this study, entrepreneurship education was explored from the perspective of the combination of psychology and literary ethics, with the purpose of studying the entrepreneurial behavior of Chinese American college students and promoting the development of entrepreneurship education. Based on the analysis of self-efficacy, the correlations among entrepreneurial intention, entrepreneurship education, and entrepreneurial efficacy of the research samples were analyzed. First, through the questionnaire design, the research samples and the measurement scales of each research variable were determined, and the survey results and the reliability of the scale were analyzed and tested. Second, based on the variance analysis and regression analysis methods, a descriptive statistical analysis was performed on the correlations among entrepreneurship education, entrepreneurial intentions, and entrepreneurial efficacy among Chinese American college students. Finally, the idea of literary ethics was integrated into entrepreneurship education, entrepreneurial intentions, and entrepreneurial self-efficacy, and the correlation structure model was constructed. The intermediary role of entrepreneurial efficacy in entrepreneurship education and entrepreneurial intention was tested. In addition, the individual gender and family entrepreneurial behaviors were considered. The results show that the valid response rate of the questionnaire, is satisfactory at, 96.49%; the reliability and validity of the scales of the research variables are satisfactory; the Cronbach’s Alpha reliability coefficient values are all above 0.80; and the fitting results of the confirmatory factors are satisfactory. The regression analysis results show significant correlations among entrepreneurship education, entrepreneurial intentions, and entrepreneurial efficacy among Chinese American college students. Entrepreneurial efficacy has a partially intermediary role in the two dimensions of entrepreneurship education and entrepreneurial intention. Individual gender and family entrepreneurial behaviors have moderating effects, on the entrepreneurial efficacy levels of college entrepreneurs. From the perspectives of psychology and literary ethics, the above results have positive effects on the development of entrepreneurship education.